Elastic Properties and the Band Gap of AlNxP1-x Semiconductor Alloy: A Comparative Study of Various Ab Initio Approaches - M. P. Polak; M. J. Winiarski; K. Wittek; P. Scharoch (Advances in Materials Science and Engineering)
Structural and elastic properties of AlNxP1-x, a novel semiconductor alloy, are studied from the first principles in both zinc-blende and wurtzite structures. Performances of the finite difference (FD) method and the density functional perturbation theory (DFPT) are tested and compared. Both of these methods are applied to two different approaches of alloy simulation, a supercell of 16 and 32 atoms (for zinc-blende and wurtzite structures, resp.) and the alchemical mixing (AM) method, where the pseudopotentials are mixed in an appropriate way to form an alloy. All elastic properties, including the elastic tensors, elastic moduli, Poisson’s ratio, B/G, and relaxation coefficient, as well as lattice parameters are calculated using all said methods. Conclusions about the use of the approaches investigated in this paper and about their performance are drawn. In addition, in both crystal structures, the band gap is studied in the whole composition range using the MBJLDA functional. The band gap bowings are unusually high, which confirms earlier reports.